2023
DOI: 10.31545/intagr/176300
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the roasting level on the content of bioactive and aromatic compounds in Arabica coffee beans

Robert Rusinek,
Bohdan Dobrzański Jr.,
Marzena Gawrysiak-Witulska
et al.

Abstract: In the present study, three degrees of roasting (light, medium, and dark), which significantly differentiate the properties of coffee beans, were analyzed. Additionally, the effect of the roasting level on the profile of volatile and biologically active compounds, including chlorogenic acids, tocopherols, and caffeine, was determined. Light-roast coffee beans, referred to as the Cinnamon roast, were obtained at 198°C. In turn, American roast beans were obtained at 212°C before the second crack, and dark beans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Initially, the CGA concentration was 472 mg L −1 and, as expected, it decreased for all reference roasting temperature sets. In the beginning, the degradation rate was higher than towards the end for all four temperatures [21]. However, for the 200 • C roasting, the last two samples exhibited nearly identical concentrations at 65 mg L −1 and 63 mg L −1 , indicating minimal change within 180 s. This contrasted with the initial breakdown of CGA, which exceeded 30% within the same timeframe.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Initially, the CGA concentration was 472 mg L −1 and, as expected, it decreased for all reference roasting temperature sets. In the beginning, the degradation rate was higher than towards the end for all four temperatures [21]. However, for the 200 • C roasting, the last two samples exhibited nearly identical concentrations at 65 mg L −1 and 63 mg L −1 , indicating minimal change within 180 s. This contrasted with the initial breakdown of CGA, which exceeded 30% within the same timeframe.…”
Section: Discussionmentioning
confidence: 83%
“…These volatile compounds, including aldehydes, ketones, and heterocyclic compounds, contribute significantly to the aroma and flavor profile of roasted coffee. Rusinek et al [21] demonstrated that different roasting levels generate varying levels of phenolic compounds, caffeine, and tocopherols, with significant differentiation in the coffee bean's chemical properties. The extent and variety of compounds formed through the Strecker degradation depend on several factors, including the types and concentrations of amino acids present, roasting temperature and duration, and the moisture content of the coffee variety.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazines represent characteristic CCV aroma compounds, which are rarely present in European vinegar, like red wine or sherry vinegar. Pyrazines are commonly found in roasted food and beverages, such as coffee, contributing to the desirable roasted flavor [ 28 , 29 ]. They are likely products of the Maillard reaction via Strecker degradation.…”
Section: The Biochemical Generation Of Key Aromas During the Brewing ...mentioning
confidence: 99%
“…Principal component analysis (PCA) is one of the simplest multivariate methods and an unsupervised technique for data clustering (Karami et al, 2020a;Karami et al, 2020b;Rusinek et al, 2024). It is usually used to reduce the dimensionality of the data, where the best results are obtained when the data are highly correlated, positively or negatively (Abdullah et al, 2015).…”
Section: Chemometrics Analysis and Neural Networkmentioning
confidence: 99%